The Psychology of Exclusivity - Jollimore, Troy (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2008)
Friendship and romantic love are, by their very nature, exclusive relationships. This paper suggests that we can better understand the nature of the exclusivity in question by understanding what is wrong with the view of practical reasoning I call the Comprehensive Surveyor View. The CSV claims that practical reasoning, in order to be rational, must be a process of choosing the best available alternative from a perspective that is as detached and objective as possible. But this view, while it means to be neutral between various value-bearers, in fact incorporates a bias against those value-bearers that can only be appreciated from a perspective that is not detached—that can only be appreciated, for instance, by agents who bear long-term commitments to the values in question. In the realm of personal relationships, such commitments tend to give rise to the sort of exclusivity that characterizes friendship and romantic love; they prevent the agent from being impartial between her beloved’s needs, interests, etc., and those of other persons. In such contexts, I suggest, needs and claims of other persons may be silenced in much the way that, as John McDowell has suggested, the temptations of immorality are silenced for the virtuous agent.